Permafrost evolution in the Swiss Alps in a changing climate and the role of the snow cover - Luetschg, M; Haeberli, W (Taylor & Francis, 2005)
The snow cover plays a decisive role on Alpine permafrost distribution with respect to its insulating properties and strong short-wave reflectivity. The complex interaction processes between atmosphere, snow cover and permafrost complicate direct predictions of the effect of changing climate parameters on ground temperatures and permafrost distribution with respect to snow cover thickness and snow period variations. In this study, the soil-extended version of the one-dimensional mass and energy balance model SNOWPACK was applied to study the ground thermal influence of realistic climate change scenarios of changing mean annual air temperatures, and summer and winter precipitation. The increasing air temperatures of two climate scenarios combined with the effect of earlier snow disappearance in spring cause warmer ground temperatures throughout the whole soil profile and steadily increasing active layer depth. From the resulting mean annual ground surface temperature changes under these climate scenarios, the lower limit of permafrost occurrence in the Swiss Alpine region is estimated to be raised between 170 m and 580 m over a period of 80 years. The presented simulation results provide an estimation of the magnitudes of climate change impact on permafrost distribution, including the complex interaction processes between atmosphere, snow cover and permafrost.